Pengaruh Tata Kelola Perusahaan Terhadap Manajemen Laba - Siti Nur Haliza; Suwarno Suwarno (Universitas Muhammadiyah Gresik, 2022)
The purpose of this research to examine the effect of corporate governance on earnings management to manufacture companies that listed in the Indonesia Stock Exchange during the period 2017-2019. The independent variables used in this study are the size of the board of commissioners, audit committee, and institutional ownership.The sample selection by purposive sampling method and 107 companies qualified as sample or 214 observations. This hypothesis testing in this research used multiple linier regression model. Partially, the size of the board of commissionersandaudit committeehas a significant effect on earnings management. Howeverinstitutional ownership had noeffect on earnings management.